Comparison of techniques to reconstruct VHE gamma-ray showers from multiple stereoscopic Cherenkov images - Hofmann, Werner; Jung, I.; Konopelko, A.; Krawczynski, H.; Lampeitl, H.; Pühlhofer, Gerd (Astroparticle physics, 2000)
For air showers observed simultaneously by more than two imaging atmospheric Cherenkov telescopes, the shower geometry is overconstrained by the images and image information should be combined taking into account the quality of the images. Different algorithms are discussed and tested experimentally using data obtained from observations of Mkn 501 with the HEGRA IACT system. Most of these algorithms provide an estimate of the accuracy of the reconstruction of shower geometry on an event-by-event basis, allowing, e.g., to select higher-quality subsamples for precision measurements.
Available online 29 March 2000
Gesehen am 18.11.2020